Designing a medicalized wellness service: balancing hospitality and hospital features. Issue 9 (9th June 2017) - Russell-Bennett, Rebekah; Glavas, Charmaine; Previte, Josephine; Härtel, Charmine E. J.; Smith, Geoff
ABSTRACT: Medicalized environments around the world are challenged with making trade-offs between the clinical nature of the service and the customer service elements needed to deliver the service. Many medicalized wellness services have yet to achieve an effective balance between their hospitality and hospital features to generate loyalty (repeat patronage). We present a case study of a blood service organization in a developed country that, at the time of data collection (2011), was working to resolve tension between clinical goals and expectations of Millennial donors. The results identified seven principles: 'control over booking and service interactions'; 'build social connections'; 'offer a luxury, indulgent experience'; 'build relationship with customer beyond the "medical" procedure'. The three remaining principles related to hospital-like features: 'hide the functional/medical features of the service experience'; 'demystify the "hidden" processes'; 'ability for the physical service environment to be modified by the customer'.